The Effect of using a mixture of maggot (Hermetia illucens) and wolffia (Wolffia arrhiza) flour on the growth of tilapia (Oreochromis niloticus) - Budi Prasetyo; Anisa Risqi Romadhona (Open Science and Technology, 2023)
Tilapia is one of the most popular freshwater fish commodities, owing to its thick meat texture and delicious taste. Rations procurement becomes one of the problematic things in tilapia farming business, because the rations price is continuously increase due to the increasing price of fish meal as the main source of protein. Maggot and wolffia are natural ingredients that can be used as an alternative to fish meal because both contain high protein. This study was conducted in January 2021 for 30 days in Batu Raja Village, North Sungkai Subdistrict, North Lampung. This study employed complete randomized design with 4 treatments and 4 replications. The observed population were 160 tilapia with observation parameters consisted of absolute weight growth, specific growth rate (SGR), absolute length growth, feed conversion value (FCR), water temperature, and water pH. Data were analyzed using ANOVA test, followed by LSD test. The best results were achieved by P3 treatment (70% maggot flour and 30% wolffia flour), which has generated the average absolute weight growth of 8.75 gr, SGR value of 29.25%, average absolute length growth of 4.1 cm, and FCR value of 3.6. Water quality parameters showed the average temperature of 28oC and pH of 6.77. Nila merupakan salah satu komoditas ikan air tawar yang banyak digemari oleh masyarakat, dikarenakan ikan ini memiliki tekstur daging yang tebal serta rasa yang lezat. Dalam usaha budidaya ikan nila, pakan merupakan salah satu hal yang kerap menjadi permasalahan, dikarenakan harga pakan yang terus mengalami peningkatan yang disebabkan oleh terus meningkatnya harga tepung ikan sebagai sumber protein utama. Belatung dan wolffia merupakan salah satu bahan alam yang dapat dijadikan alternatif pengganti tepung ikan karena keduanya memiliki kandungan protein cukup tinggi. Penelitian ini dilaksanakan pada Januari 2021 selama 30 hari di Desa Batu Raja, Kecamatan Sungkai Utara, Kabupaten Lampung Utara. Penelitian ini menggunakan rancangan acak lengkap dengan 4 perlakuan dan 4 pengulangan. Populasi dalam penelitian ini berupa 160 ekor ikan nila dengan parameter pengamatan meliputi pertumbuhan bobot mutlak, laju pertumbuhan spesifik (SGR), panjang mutlak, nilai konversi pakan (FCR), suhu air, dan pH air. Data dianalisis dengan uji ANOVA, dilanjutkan dengan uji BNT. Hasil penelitian menyatakan bahwa perlakukan P3 (70% tepung belatung dan 30% tepung wolffia) memberikan hasil terbaik, yaitu rerata pertumbuhan bobot mutlak 8,75 gr, nilai SGR 29,25%, rerata pertumbuhan panjang mutlak 4,1 cm, dan nilai FCR 3,6. Parameter kualitas air menunjukkan rerata suhu 28 oC dan pH 6,77.